PENGARUH AKUNTABILITAS KERJA TERHADAP KUALITAS PELAYANAN PADA PT. POS INDONESIA (PERSERO) MANADO - MOKOAGOW, MELIANI; OGOTAN, MARTHA; LONDA, VERY (JURNAL ADMINISTRASI PUBLIK, 2018)
Accountability's work is one of the determining factors for quality of service. In addition, there is anotherfactor in determining both the poor quality of service. Accountability's work is felt still less in improving thequality of service that can be seen from the work procedures and on the evaluation of the implementationof the policy. This study describes two variables namely variables and variable work accountability qualityservice. The purpose of this study was to analyze the influence of the quantity of work towards accountabilityquality service. Variable working accountability tested using four dimensions and variable service qualitytested using five dimensions. This research was conducted at PT. Pos Indonesia (Persero) in Manado. Theresearch method used is the quantitative methods with the dissemination of the questionnaire to therespondent as much as thirteen rounds of questions and sample as many as thirty employees at PT PosIndonesia (Persero) in Manado. Sampling technique used was random sampling with simple linearregression analysis using SPSS program assistance. A simple linear regression analysis results showed asmany as forty-three percent of the variable akuntabilits influential work positively towards the variablequality of service. Where that accountability work positive effect on service quality.Keywords: Accountability, Service, Quality.